Communicative Language Teaching (CLT): A Strategy to Enhance Students’ Speaking Skills and Motivation - Radinsa Yola Candadila; Desi Puspitasari (Aisyah Journal of English Language Teaching (AIJELT), 2025)
Speaking is one of the foundational components of language proficiency, requiring learners to produce language spontaneously with fluency and accuracy, while motivation plays a key role in sustaining learners' engagement and willingness to communicate. In English as a Foreign Language (EFL) classrooms, both speaking ability and motivation remain common challenges. Communicative Language Teaching (CLT), which emphasizes interaction and authentic language use, can help students to develop both aspects by involving learners in real-life communicative tasks such as role plays. This study aimed to investigate the effectiveness of CLT in improving the speaking skills and learning motivation of seventh graders at SMPN 3 Kota Madiun. To provide a comparative measure, the Audio-Lingual Method (ALM), a traditional, drill-based method, was used with a control group. Employing a quasi-experimental design, students were divided into experimental and control groups. Data were gathered through speaking performance tests and motivation questionnaires, and then were analyzed using SPSS 25 with the Mann-Whitney U test, Independent Sample t-test, and N-Gain. The results demonstrated that CLT significantly enhanced both students’ speaking abilities (U = 259.000; p = 0.002) and motivation (p = 0.000) compared to ALM, with a moderate N-Gain effectiveness (56–75%) for the CLT group and minimal improvement (<40%) in the ALM group. These findings confirm CLT as a more effective and engaging instructional method in EFL classrooms.